Effect of High-Flow Nasal Cannula for Hypoxemia Following Sun's Procedure in Acute Aortic Dissection Type a Patients - Yan, ChaoJun; Zhang, Jianrong; Wu, Yi; Yao, Jie; Li, Jun; Zhang, Xianpu; Cheng, Yongbo; Liu, Xin; Yi, Jianguang; Lin, Deqin; Yu, Sanjiu; Guo, Mei; et al. (Frontiers in Surgery, 2021)
Background: Patients with acute aortic dissection type A (AADA) often have hypoxemia (partial pressure of oxygen [PaO2]/fraction of inspired oxygen [FiO2] <300 mmHg) before weaning in the intensive care unit (ICU). This study compared the efficacy of high-flow nasal cannula (HFNC) with that of conventional oxygen therapy (COT) in patients with AADA following Sun's procedure. Methods: The medical records of 87 adult patients with AADA who underwent Sun's procedure and met the inclusion criteria (PaO2/FiO2 <300 mmHg before weaning) were retrospectively analyzed. After surgery, 41 patients were treated with HFNC and 46 were treated with COT. The oxygenation level, FiO2, partial pressure of carbon dioxide, heart rate, respiratory rate, subjective discomfort, and reintubation rate were recorded. The difference in lung volume loss between the HFNC and COT groups was assessed using the radiological atelectasis score (chest radiograph) or calculated from three-dimensional (3D) reconstructed computed tomography (CT) images. Results: From day 1 to day 5 after weaning, there was no significant difference in PaO2/FiO2 between the HFNC and COT groups, although the FiO2 was significantly lower in the HFNC group than in the COT group (P < 0.05). Further studies indicated that the percentage of lung volume loss (pleural effusion and/or pulmonary atelectasis) by 3D reconstruction of CT images at 4–8 days post-operation was significantly lower in the HFNC group (P < 0.05). The subjective experience of breathing discomfort, reintubation rate, and length of stay in the ICU were significantly reduced in the HFNC group (P < 0.05). There was no significant difference in readmission to the ICU and in-hospital mortality between the two groups. Conclusions: HFNC can be used as an effective oxygen therapy for AADA patients with hypoxemia after Sun's procedure.